Thematic Study of Poverty in the Al-Qur’an (Islamic Economic Perspective) - Yuliansyah; Achmad Abubakar; Hasyim Hadade (Institute of Computer Science (IOCS), 2023)
In the Islamic perspective, poverty arises due to structural causes, namely because of human crimes against nature (QS Ar Ruum: 41); indifference and greed of the rich (QS Ali Imran: 180); some humans are tyrannical, exploitative, and oppressive to some other humans (QS At Taubah: 34); concentration of political, bureaucratic, and economic power in one hand (QS Al Qashash; 1-88); poverty arises due to external turmoil such as natural disasters or wars so that the country that was originally rich turns into poverty. (QS Saba': 14-15). Poverty alleviation strategies in an Islamic perspective include: 1) Encouraging economic growth that provides broad benefits to the community (pro-poor growth); 2) Encouraging the creation of a state budget that favors the interests of the people (pro-poor budgeting); 3) Encouraging infrastructure development that provides broad benefits to the community (pro-poor infrastructure); 4) Encouraging the provision of basic public services that favor the wider community (pro-poor public services); and 5) Encouraging equity and income distribution policies that favor the poor (pro-poor income distribution).